Electrocardiographic assessments and cardiac events after fingolimod first dose – a comprehensive monitoring study. Issue 1 (December 2017) - Limmroth, Volker; Ziemssen, Tjalf; Lang, Michael; Richter, Stephan; Wagner, Bert; Haas, Judith; Schmidt, Stephan; Gerbershagen, Kathrin; Lassek, Christoph; Klotz, Luisa; Hoffmann, Olaf; Albert, Christian; et al.
Abstract Background First dose observation for cardiac effects is required for fingolimod, but recommendations on the extent vary. This study aims to assess cardiac safety of fingolimod first dose. Individual bradyarrhythmic episodes were evaluated to assess the relevance of continuous electrocardiogram (ECG) monitoring. Methods START is an ongoing open-label, multi-center study. At the time of analysis 3951 patients were enrolled. The primary endpoints are the incidence of bradycardia (heart rate < 45 bpm) and second-/third-degree AV blocks during treatment initiation. The relevance of Holter was assessed by matching ECG findings with the occurrence of clinical symptoms as well as by rigorous analysis of AV blocks with regard to the duration of pauses and the minimal heart rate recorded during AV block. Results Thirty-one patients (0.8%) developed bradycardia (<45 bpm), 62 patients (1.6%) had second-degree Mobitz I and/or 2:1 AV blocks with a lowest reading (i.e. mean of ten consecutive beats) of 35 bpm and the longest pause lasting for 2.6 s. No Mobitz II or third-degree AV blocks were observed. Only one patient complained about mild chest discomfort and fatigue. After 1 week, there was no second-/third-degree AV block. Conclusions Continuous Holter ECG monitoring in this large real-life cohort revealed that bradycardia and AV conduction abnormalities were rare, transient and benign. No further unexpected abnormalities were detected. The data presented here give an indication that continuous Holter ECG monitoring does not add clinically relevant value to patients' safety. Trial registration NCT01585298 ; registered April 23, 2012.